Penentuan Microcontroller Unit (MCU) Terbaik berdasarkan Pembobotan Objektif - Andre Hasudungan Lubis; Solly Aryza; sutrisno (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
A Microcontroller Unit (MCU) plays an important role in technology developments. It used as the data input receiver, processing, and presenting data output tallied to the program built. Various MCUs are provided inmarket with numerous types and architectures of them. Hence, a decision model is necessity to aid the select the best between MCUs. The WASPAS Method was employed along with the CRITIC method as the objective weighting for the criteria. The criteria used are the instruction set, memory architecture, total of I/O pins, power consumption, price, RAM size, and processing speed. The result pointed out that ESP32 selected as the best MCU between the others. This study provides recommendations to prospective buyers or users to decide the best MCU